Prasasti Kintamani E Kajian Epigrafi - Prama Saputra, I Gede; Palupi Titasari, Coleta (Humanis, 2018)
This study is concentrated on a group of inscriptions currently stored in Bale Agung Kintamani Temple . Therefore the problemsis consists of two questions, those are: how the linguistic aspects of the inscription and aspects of social institutions enclosed to the inscription . The are two phasesresearch method. Data collection is done through libraryresearch and observation to documentation result. The collected dataare analyzed through morphological analysis and qualitative analysis.The research results showed that the Kintamani E inscription contains several aspects of language such as the using of affixation are Perfix: (di-, sa-, a- or ma-, pa-, ka-, pari-, Infix: -um- , -in-, suffixes: -nya-, -aken, - ?n, konfiks: (pa - an), (ma - an), (ka - an), (ma - ak?n), (pa - nya), (saka-nya).The social orders involved the political aspect, economic aspect, religious aspect and social aspects contained in the inscription very possibly reflectedthe society at that time